PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN KEWIRAUSAHAAN KELAS X SMK TELKOM PEKANBARU - Hasana Hasana; Sumarno Sumarno; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This study aims to determine the effect of parental education and parents' income on student achievement in entrepreneurship subjects in class X Pekanbaru Telkom Vocational School. The population in this study were students of class X Telkom Telkom Vocational School totaling 218 students.The sample was taken by proportional random sampling technique and Taro Yamane formula as many as 69 students. Analysis of the data used is path analysis. The results of the study explain that education has a direct positive effect on income of 0.469. Parental education has a direct effect on students' entrepreneurial learning achievement of 0.256 and indirectly by 0.184 with a total of 0.440. Parent income has a direct positive effect on learning achievement of 0.393.Key Words: Socio-Economic Status of Parents and Learning Achievements